Retinal arterial–venous pulse delay: a new specific marker for a carotid–cavernous fistula - Linton, Edward F.; Tedeschi, Thomas R.; Ahmad, Noor-Us-Sabah; Wang, Jui-Kai; Kardon, Randy H. (Frontiers in Ophthalmology, 2023)
Purpose: To describe ocular blood flow changes in eyes affected by a carotid-cavernous fistula (CCF) using Laser Speckle Flowgraphy. We hypothesized that imaging blood flow velocity waveforms in retinal arterioles and venules simultaneously would reveal specific characteristics of an arteriovenous connection.Design: Observational case series with retrospective case-control analysis.Methods: Five patients with CCF underwent measurement of ocular blood flow using Laser Speckle Flowgraphy. Blood flow was compared retrospectively to a control group of healthy subjects (n=32) and patients with elevated intraocular pressure or venous outflow impairment without an AV fistula (n=40). Outcomes were derived from arteriole and venule blood flow velocity waveforms, including A-V phase delay and flow pulsatility.Results: Presence of an active CCF was associated with an increased delay in the peak velocity measured in the retinal venule (10.7 ± 2.2% of the cardiac cycle duration) compared to unaffected fellow eyes (1.8% ± 0.2, p=0.05) or control eyes of normal subjects (2.7% ± 0.3, p=0.02). This delay disappeared after fistula thrombosis, and was not present in eyes with CRVO, glaucoma, NAION, or papilledema. Venule blood flow velocity decreased during systole (and in some cases momentarily stopped), leading to a delayed pulse with greater amplitude in the venules compared to fellow eyes and normal controls after normalizing to the arteriole amplitude (1.71±0.3 vs 0.54±0.03 vs 0.59±0.02, p=8.0E-12). This specific arterial-venous delay could also be identified in scanning laser ophthalmoscope (SLO; Spectralis) video.Conclusions: Laser Speckle Flowgraphy reveals dynamic retinal vascular changes in eyes affected by a carotid-cavernous fistula that is not present in healthy controls or patients with other eye conditions, and which reverses with treatment.